New insights into the mechanisms of Treg function. Issue 4 (August 2015) - Rothstein, David M.; Camirand, Geoffrey
Abstract : Purpose of review: CD4 + Foxp3 + regulatory T cells (Tregs) are crucial in controlling immunity and self-tolerance. Consequently, in transplantation, Tregs play a central role in inhibiting acute rejection and promoting allograft tolerance. A more complete understanding of Treg biology may lead to novel therapeutic approaches to enhance Treg numbers and function. Recent findings: The maintenance of self-tolerance in nonlymphoid tissues requires the differentiation of Tregs in secondary lymphoid organs from naïve-like central Tregs into effector Tregs. Antigen and environmental cues guide this Treg differentiation, which parallels the types of adaptive immune responses taking place, allowing them to enter and function within specific nonlymphoid tissues. In addition to controlling inflammation, tissue-infiltrating Tregs unexpectedly regulate nonimmune processes, including metabolic homeostasis and tissue repair. Finally, Tregs can be directly and specifically targeted in vivo to augment their numbers or enhance their function in both secondary lymphoid organs and nonlymphoid tissues. Summary: Tregs exhibit a previously unrecognized breadth of function, which includes tissue-specific specialization and the regulation of both immune and nonimmune processes. This is of particular importance in transplantation since allo-reactive memory T cells can act directly within the allograft. Thus, therapeutic approaches may need to promote Treg function in transplanted tissue, as well as in secondary lymphoid organs. Such therapy would not only prevent inflammation and acute rejection, but may also promote nonimmune processes within the allograft such as tissue homeostasis and repair.